Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To simplify the expression [tex]\((4 - i)(-3 + 7i) - 7i(8 + 2i)\)[/tex] into the form [tex]\(a + bi\)[/tex], where [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are rational numbers, follow these steps:
1. Expand the first product [tex]\((4 - i)(-3 + 7i)\)[/tex]:
[tex]\[ \begin{aligned} (4 - i)(-3 + 7i) &= 4 \cdot (-3) + 4 \cdot (7i) + (-i) \cdot (-3) + (-i) \cdot (7i) \\ &= -12 + 28i + 3i - 7i^2 \\ &= -12 + 31i - 7(-1) \quad \text{(since } i^2 = -1) \\ &= -12 + 31i + 7 \\ &= -5 + 31i \end{aligned} \][/tex]
2. Expand the second product [tex]\((-7i)(8 + 2i)\)[/tex]:
[tex]\[ \begin{aligned} (-7i)(8 + 2i) &= (-7i)(8) + (-7i)(2i) \\ &= -56i - 14i^2 \\ &= -56i - 14(-1) \quad \text{(since } i^2 = -1) \\ &= -56i + 14 \end{aligned} \][/tex]
3. Combine the results of the two products:
[tex]\[ \begin{aligned} (-5 + 31i) + (14 - 56i) &= -5 + 31i + 14 - 56i \\ &= (-5 + 14) + (31i - 56i) \\ &= 9 - 25i \end{aligned} \][/tex]
So, the simplified form of [tex]\((4 - i)(-3 + 7i) - 7i(8 + 2i)\)[/tex] is:
[tex]\[ 9 - 25i \][/tex]
Thus, in the form [tex]\(a + bi\)[/tex], we have [tex]\(a = 9\)[/tex] and [tex]\(b = -25\)[/tex].
1. Expand the first product [tex]\((4 - i)(-3 + 7i)\)[/tex]:
[tex]\[ \begin{aligned} (4 - i)(-3 + 7i) &= 4 \cdot (-3) + 4 \cdot (7i) + (-i) \cdot (-3) + (-i) \cdot (7i) \\ &= -12 + 28i + 3i - 7i^2 \\ &= -12 + 31i - 7(-1) \quad \text{(since } i^2 = -1) \\ &= -12 + 31i + 7 \\ &= -5 + 31i \end{aligned} \][/tex]
2. Expand the second product [tex]\((-7i)(8 + 2i)\)[/tex]:
[tex]\[ \begin{aligned} (-7i)(8 + 2i) &= (-7i)(8) + (-7i)(2i) \\ &= -56i - 14i^2 \\ &= -56i - 14(-1) \quad \text{(since } i^2 = -1) \\ &= -56i + 14 \end{aligned} \][/tex]
3. Combine the results of the two products:
[tex]\[ \begin{aligned} (-5 + 31i) + (14 - 56i) &= -5 + 31i + 14 - 56i \\ &= (-5 + 14) + (31i - 56i) \\ &= 9 - 25i \end{aligned} \][/tex]
So, the simplified form of [tex]\((4 - i)(-3 + 7i) - 7i(8 + 2i)\)[/tex] is:
[tex]\[ 9 - 25i \][/tex]
Thus, in the form [tex]\(a + bi\)[/tex], we have [tex]\(a = 9\)[/tex] and [tex]\(b = -25\)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.